2014
DOI: 10.1111/dmcn.12376
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome and cognition in Down syndrome

Abstract: ACTBArizona Cognitive Test Battery AHI Apnea-hypopnea index IED Intra-extra dimensional set shift OSAS Obstructive sleep apnea syndrome PSG PolysomnographyAIM Good-quality sleep is essential for normal learning and memory. Sleep fragmentation and disrupted sleep architecture are commonly observed throughout the lifespan of individuals with Down syndrome, a condition marked by cognitive deficits emerging within the first few months of life. While obstructive sleep apnea syndrome (OSAS) is known to contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
179
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(197 citation statements)
references
References 25 publications
10
179
3
5
Order By: Relevance
“…3 Patients with DS have a higher incidence of OSA than the general pediatric population, with rates of 30% to 80%, resulting in increased morbidity and decreased quality of life for affected individuals. 4 In children, adenotonsillar hypertrophy is often a contributing factor to OSA, and adenotonsillectomy (T&A) is the initial treatment of choice. Children with DS often undergo T&A for OSA; however, up to 67% will have persistent obstructive sleep patterns, which are attributed to anatomic and physiologic differences in this population, including reduced muscular tone, macroglossia, maxillary hypoplasia, and lingual tonsil hypertrophy.…”
mentioning
confidence: 99%
“…3 Patients with DS have a higher incidence of OSA than the general pediatric population, with rates of 30% to 80%, resulting in increased morbidity and decreased quality of life for affected individuals. 4 In children, adenotonsillar hypertrophy is often a contributing factor to OSA, and adenotonsillectomy (T&A) is the initial treatment of choice. Children with DS often undergo T&A for OSA; however, up to 67% will have persistent obstructive sleep patterns, which are attributed to anatomic and physiologic differences in this population, including reduced muscular tone, macroglossia, maxillary hypoplasia, and lingual tonsil hypertrophy.…”
mentioning
confidence: 99%
“…Otras morbilidades crónicas como vicios de refracción, problemas dermatológicos y traumatológicos, SAHOS y epilepsia fueron reportados en nuestra serie con similar frecuencia a lo publicado en la literatura 28,29 , lo que motiva a tener equipos multidisciplinarios capacitados y al día con las recomendaciones internacionales para el cuidado en salud de los adolescentes con SD.…”
Section: Discussionunclassified
“…The high prevalence of sleep disorders during childhood may make children with DS particularly susceptible to ill effects during critical periods of cognitive development. Small cross sectional studies have found deficits in IQ [6], cognitive and behavioural function [74][75][76][77] and accomplishment of daily activities [78] in children with DS and co-existing sleep problems, suggesting an association between poor sleep and these deficits in this group. The age range evaluated in these studies has varied with some groups concentrating on pre-school children with DS [75][76][77] and others examining older children [6,74,78].…”
Section: Potential Impact Of Sleep Disorders In Children With Down Symentioning
confidence: 99%
“…It is the most common genetic cause of significant intellectual disability [5]. The condition is characterised by decline of IQ during infant and toddler years, well-documented impairments in the assimilation and expressive use of language, as well as in cognitive flexibility and memory [6]. Large inter-individual differences are seen within the DS population and numerous factors including genetics, epigenetics, early neural development and the environment are thought to have a role in how the DS phenotype expresses itself in each individual [7].…”
Section: Introductionmentioning
confidence: 99%